2020
DOI: 10.3390/mi11090798
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Nose Radius on the Machining Forces Induced during AISI-4140 Hard Turning: A CAD-Based and 3D FEM Approach

Abstract: The present study investigated the performance of three ceramic inserts in terms of the micro-geometry (nose radius and cutting edge type) with the aid of a 3D finite element (FE) model. A set of nine simulation runs was performed according to three levels of cutting speed and feed rate with respect to a predefined depth of cut and tool nose radius. The yielded results were compared to the experimental values that were acquired at identical cutting conditions as the simulated ones for verification purposes. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 37 publications
(49 reference statements)
1
13
0
Order By: Relevance
“…At the pre-processing stage, the workpiece was modelled as deformable and meshed with approximately 32,000 to 60,000 tetrahedral elements depending on the value of the feed. The minimum element size of the mesh was set to 25% of the feed [39,40]. Moreover, a 7:1 ratio between the largest and the smallest element size of the mesh was applied to the section of the workpiece (see Figure 2b), so that the solid elements of the workpiece that participate in the removal process are created seven times smaller compared to the rest of the elements.…”
Section: Definition Of the Analysis Interfacementioning
confidence: 99%
“…At the pre-processing stage, the workpiece was modelled as deformable and meshed with approximately 32,000 to 60,000 tetrahedral elements depending on the value of the feed. The minimum element size of the mesh was set to 25% of the feed [39,40]. Moreover, a 7:1 ratio between the largest and the smallest element size of the mesh was applied to the section of the workpiece (see Figure 2b), so that the solid elements of the workpiece that participate in the removal process are created seven times smaller compared to the rest of the elements.…”
Section: Definition Of the Analysis Interfacementioning
confidence: 99%
“…Figure 2 depicts a standardized 80 • rhombic insert with its micro-geometry which comprises the cutting edge type, the chamfer angle and the chamfer width. In addition to the corner radius, the aforementioned parameters are crucial because they greatly affect the cutting forces during machining [20][21][22][23]. Moreover, according to Denkena et al [24] the cutting edge micro-geometry affects the tool life significantly due to changes in the characteristic tool wear behavior.…”
Section: Description Of Turning Insertsmentioning
confidence: 99%
“…Specifically, Figure 5a depicts the initial step of the design process. At first, the front plane of the part document is selected because it is important to define a coordinate system that will serve through the FE analysis [22]. Hence, the Z-axis must be parallel to the tangential force vector, the Y-axis must be parallel to the radial force vector and finally, the X-axis must be parallel to the feed force vector.…”
Section: Modelling Procedures Of Turning Cutting Toolsmentioning
confidence: 99%
“…The findings showed that cutting depth has a strong effect on the cutting force, the removal capability, and the material removal rate (MRR). The association between the essential parameters (nose radius, feed rate, and cutting speed) and their effect on the turning force components was investigated by Tzotzis et al [12]. The distinction between the resultant values of the cutting force factors and the simulations revealed an improvement in the association of over 89%.…”
Section: Introductionmentioning
confidence: 99%